2022
DOI: 10.3390/su142113899
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Luxury Hotel Customer Experience on Brand Love and Customer Citizenship Behavior

Abstract: The luxury hotel market has been developing rapidly recently in the Asian Market. To provide useful outcomes to hotels competing in fierce market conditions, the current study investigated the relationship between customer experience values, customer post-experience consequences, and citizenship behaviors. Our findings confirmed the valuable contribution of customer experience values (ROI and service excellence) to the development of brand satisfaction, which in turn positively influences brand commitment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
1
5
0
1
Order By: Relevance
“…This leads to more benefits to the company itself as well as to other potential customers. These results are consistent with previous research, which found that experiential value in luxury hotels has a positive impact on customer citizenship behaviour (Lin & Choe, 2022). Moreover, a positive relationship has been established between perceived value and customer citizenship behaviour in cause-related marketing on social media (Deng et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…This leads to more benefits to the company itself as well as to other potential customers. These results are consistent with previous research, which found that experiential value in luxury hotels has a positive impact on customer citizenship behaviour (Lin & Choe, 2022). Moreover, a positive relationship has been established between perceived value and customer citizenship behaviour in cause-related marketing on social media (Deng et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…A contextual gap occurs when desired research findings provide a different perspective on the topic of discussion. For instance, Liang, Wang & Zhang (2021) explored the impact of customer experience values (return on investment and service excellence) on brand satisfaction, commitment, love, and citizenship behaviors in luxury hotels. Data were collected from a survey of 400 customers who stayed at luxury hotels in China.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, a methodological gap also presents itself, for example, in their study on the impact of customer experience values (return on investment and service excellence) on brand satisfaction, commitment, love, and citizenship behaviors in luxury hotels; Liang, Wang & Zhang (2021) collected from a survey of 400 customers who stayed at luxury hotels in China. Partial least squares structural equation modeling was used to test the research model.…”
Section: Resultsmentioning
confidence: 99%
“…These limitations provide avenues for further research to enhance the understanding of the concept of perceived corporate philanthropy. Therefore, it would be intriguing for upcoming research to explore additional ramifications of PCP, encompassing aspects such as brand equity, brand personality, brand attachment, and consumers' experience in line with the work in [131], among others. Moreover, it would be worthwhile to examine a different sector, distinct from the luxury industry, in order to validate the PCP scale.…”
Section: Discussionmentioning
confidence: 99%